An Analysis of Land Certificate Service Management at the Land Office of East Halmahera Regency - Sudin, Idris; Fabanyo, Amir (International Journal of Education, Information Technology, and Others, 2024)
Land certificate service is an implementation practice of land office’s institutional function in the context of land registration and issuance of land certificates, in order to guarantee a legal certainty and provide a legal protection for land owners. Somehow in the implementation, there are some insights or judgements from the people who used this service to process certificates regarding to service performance at the land office. There are some insights such as: the requirements are difficult, the procedures are complicated, the completion time is uncertain, the terms take a long time, the costs are expensive and the assessment is not transparent. This is cannot be separated from the aspects of service management. This research aims to analyse and find out the extent of the implementation of land certificate services at the East Halmahera Regency Land Office, then to analyse and find out in depth the factors that support and impede the implementation of land certificate services at the East Halmahera Regency Land Office. This research is qualitative research used a descriptive approach. Based on the research results, there are the following conclusions: First, the implementation of land certificate service management at the East Halmahera Regency Land Office has not been successively well, which has an impact on improving service performance and providing satisfaction for the entire community. From the planning aspect, there are clear targets and service program strategies as well as resources in the form of budget availability, however at the implementation stage there are deficiencies in the aspect of guaranteeing certainty of timely completion. However, from the aspect of actuating ability, in terms of motivation to carry out actions with awareness to achieve service goals, there are employees who still weak in the responsiveness indicator. For example, the employee while serving the community, they keep chats with fellow employees about something that is not related to the work or service being carried out, so the work are take more time to be done; Second, there are supporting factors in the form of a strategic office location in providing services as well as a comfortable office atmosphere. However, there is a constraining factor that has a real influence, namely the lack of employees in accordance with the workload of services that must be carried out. Based on the result conclusions above, the recommendations/suggestions of this research are: First, the Head of the East Halmahera Regency Land Office needs to increase the application of employee discipline at work and provide action or sanctions to employees who are not disciplined at work. In addition to efforts to increase the number and quality of employee human resource capabilities according to the need for competency and skills needed to ensure that the implementation of land certificate service management can run effectively and efficiently in improving the performance of good land certificate services; Second, every employee must have the awareness and work motivation to ensure that aspects of land certificate service management at the East Halmahera Regency Land Office can run well. In this way, it can increase public satisfaction in receiving services